2008
DOI: 10.1016/j.gep.2008.06.006
|View full text |Cite
|
Sign up to set email alerts
|

uPARAP expression during murine lung development

Abstract: Lung remodeling requires active collagen deposition and degradation. Urokinase plasminogen activator receptor-associated protein (uPARAP), or Endo 180, is a cell surface receptor for collagens, which leads to collagen internalization and degradation. Thus, uPARAP-mediated collagen degradation is an additional pathway for matrix remodeling in addition to matrix remodeling mediated by matrix metalloproteinases and cathepsins. Using immunohistochemistry, we demonstrate extensive uPARAP expression in the mesenchym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Although uPARAP internalizes collagen I and collagen IV, we previously demonstrated that uPARAP colocalized most closely with collagen IV, not collagen I, during lung development (6). Collagen type IV is a major component of the alveolar basement membrane basal lamina.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Although uPARAP internalizes collagen I and collagen IV, we previously demonstrated that uPARAP colocalized most closely with collagen IV, not collagen I, during lung development (6). Collagen type IV is a major component of the alveolar basement membrane basal lamina.…”
Section: Discussionmentioning
confidence: 86%
“…We previously demonstrated high expression of uPARAP in the mesenchyme throughout lung development (6). Despite the high expression of uPARAP in the developing lung, development proceeds normally in uPARAP 2/2 mice, and is not associated with any differences in matrix metalloproteinase (MMP), tissue inhibitor of metalloproteinases, or collagen expression in the lung (6).…”
mentioning
confidence: 99%
“…These include pathological conditions such as cancer, fibrosis and osteoarthritis [17], [21], [22], [23], [24], [25], [26], [27], [28], [29], and under normal physiological conditions, expression has been observed in the developing lung and in the bones [18], [30]. In addition, uPARAP has been found to be functionally involved in protection against tissue fibrosis [21], [28], [29] and in promotion of breast tumor progression [24], [31] and possibly glioma invasion [25].…”
Section: Introductionmentioning
confidence: 99%
“…This protein, designated uPARAP in the following, is a member of the mannose receptor family of endocytic receptors (22)(23)(24). uPARAP is expressed at sites with ongoing tissue remodeling (25)(26)(27)(28) and functions in delivering collagens for intracellular degradation in lysosomes (29 -35). In some processes the receptor operates together with extracellular collagen degradation mechanisms and it is effective in internalizing the large cleavage products resulting from initial extracellular collagenase digestion (36 -38).…”
mentioning
confidence: 99%